Peran Istri dalam Pengambilan Keputusan Standar Operasional Prosedur (SOP) Petik Merah Kopi Robusta di Temanggung (Studi Kasus Petani Kopi Desa Gesing) - Widodo, Ananda Rizky; Suwarto, Suwarto; Sugihardjo, Sugihardjo (Universitas Muhammadiyah Semarang, 2023)
This study aims to examine the roles of the wife in making red coffee-picking decisions in Temanggung Regency, Central Java. This research focuses on identifying and understanding the role of the wife in the decision-making process related to picking red coffee, as well as the factors that influence their involvement and contribution to these activities. The research method used is a qualitative approach with in-depth interview techniques and direct observation. Data were collected from several coffee farming families in Temanggung, including from farmers who have active participation from their wives in farming activities. The results of the study show that the role of the wife in making decisions on picking red coffee in Temanggung contributes to various stages of the agricultural process, from land preparation to post-harvest. The role of the wife includes selecting coffee varieties, setting planting schedules, selecting methods and timing of picking, and planning the use of resources and labor. In addition, the wife also plays a role in managing family finances and allocating resources for investment in coffee cultivation. The wife's social role is also seen in forming good relations with other community members, such as in organizing cooperation activities or participating in farmer organizations.